Gambaran Pengetahuan Tentang Pemeliharaan dan Kebersihan Gigi dan Mulut pada Siswa Kelas IV SDN 13 Sesetan Denpasar Selatan Tahun 2025: Volume 13 No.1 - Ni Nyoman Dewi Supariani; Ni Wayan Arini; Asep Arifin Senjaya; Ni Kadek Rupini Yelia; Ni Made Sirat (Jurnal Kesehatan Gigi (Dental Health Journal), 2026)
Dental and oral health issues remain a significant concern in public health, especially among elementary school-aged children. This condition can affect their learning process and overall growth and development. This study aims to determine the level of knowledge and the condition of dental and oral hygiene among 49 fourth-grade students at SD Negeri 13 Sesetan, South Denpasar, in 2025. The method used is descriptive qualitative. Data were collected through a questionnaire consisting of 10 multiple-choice questions regarding dental and oral health knowledge, as well as direct examination using the Oral Hygiene Index-Simplified (OHI-S). The results showed that out of 49 students, 27 (55%) had very good knowledge, 10 (20%) good, 8 (16%) fair, 3 (6%) poor, and 1 (2%) failed, with an average knowledge score of 76.7. Meanwhile, the level of dental and oral hygiene based on the OHI-S index indicated that 20 students (41%) were in the good category, 20 (41%) moderate, and 9 (18%) poor, with an average score of 1.91 (moderate category). It can be concluded that good knowledge is not fully accompanied by optimal hygiene practices.